ANISOTROPIC INVERSE DISTANCE WEIGHTING (IDW) METHOD: AN INNOVATIVE TECHNIQUE FOR RESOURCE MODELING OF VEIN-TYPE DEPOSITS - Ongarbayev, Ilyas (Nazarbayev University School of Mining and Geosciences, 2022)
The geological model is integral evaluation of natural resources. The traditional explicit geological modeling approach has been used in the industry for a long time. However, due to its time-consuming nature and inflexibility, implicit geomodelling has emerged as an alternative. Implicit modeling approaches are based on mathematical algorithms, which automatically build the geological model, thereby taking on all arduous work. In this respect, the authors propose a previously unused for modeling of categorical variables in anisotropic geological conditions, the Anisotropic Inverse Distance Weighting (IDW) method. The underlying concepts of how the proposed method works are comprehensively introduced in the methodology section. The Anisotropic IDW is explicitly oriented for modeling anisotropic domains, and the variogram analysis is vital for the proposed method. The Anisotropic IDW produces acceptable results, and to evaluate its performance, the Anisotropic IDW was compared to widely used in the industry Indicator Kriging (IK) and traditional IDW. The experimental part was implemented on synthetic and real case studies. The synthetic dataset represents a 2D modeling of two geological domains, where the modeling methods estimate the potential ore and waste domains. The synthetic case study was conducted to evaluate the capabilities of the proposed methodology compared to traditional IDW and IK and determine which one of the methods is more suited for geomodelling of veins in anisotropic conditions. The real case study was considered in 3-dimension and using the borehole assays from a vein-type gold deposit in Kazakhstan. The real case study was conducted to show that the proposed methodology might be successfully applied in real conditions. Furthermore, resource estimation was performed to compare modeling methods more comprehensively. As for the results, the Anisotropic IDW showed an acceptable performance, which is better than the traditional IDW and Indicator Kriging in both synthetic and real case studies (details in section 4). Finally, from the results of the conducted studies, it is apparent that Anisotropic IDW for veins modeling in anisotropic conditions is the most optimum method among considered.
Keywords: Type of access: Gated Access; IDW; Anisotropic IDW; Indicator Kriging; IK